A comparison of the IAS and the accounting standards in Europe and US for the real estate industry - Neves, João Carvalho das (2004)
In June 2000 the European Commission issued an updated strategy on accounting harmonisation, which was approved in June 2002 by the European Parliament. The regulation 1606/2002 states that by 2005 all listed companies in the European Union, including banks and insurance companies should conform to the international accounting standards (IAS). As a consequence it is important to analyse national standards in Europe and ensure the convergence to international standards in the best possible manner for each country and industry. There is little authoritative literature regarding the principles of accounting for the real estate industry in Europe. Real estate industry is a sector that raises special accounting issues, such as: the costing of inventories, the timing for classifying an inventory as finished goods, the timing for the recognition of cost of sales, the value and timing for recognition of revenues and the accounting of customer's guarantees. The Financial Accounting Standard Board (FASB) and the American Institute of Certified Public Accountants (AICPA) publishes specific guidelines and pronouncements dedicated to real estate issues. However there is nothing similar in European Union countries, or in the IAS (which apply to all industries). As a consequence, this paper takes the point of view of an investor or a property developer, surveys the IAS that relate to real estate development major accounting issues, and simultaneously compares each of the issues with the present accounting standards in the USA, in three major players in Europe (France, UK and Germany) and Portugal, a small country that is rarely studied. This work aims to find out how satisfactory the IAS are for standardising the accounts of real estate developers and how far the various countries analysed are from the required new standards. Therefore, it is apparent that this research is useful for property developers, accountants, and accounting regulators. We conclude that the implementation of the IAS allow for significant discretion in the Real Estate industry and consequently, in spite of some convergence across nations, it is unlikely to find uniformity of accounting across companies of this sector that engage in similar activities.